Beyond the Screen: A Systematic Review of Perception/Reception Studies in Interlingual Dubbing and Subtitling - Antonini, Rachele; Bucaria, Chiara (Journal of Audiovisual Translation, 2025)
This paper aims to provide a systematic review of English-language journal articles and book chapters that consider the audience perception/reception perspective in interlingual dubbing and subtitling, with the goal of describing the evolution of this type of empirical research over the last two decades. After establishing exclusion and inclusion criteria, the authors used four databases – Scopus, BITRA, TSB, and Web of Science – to retrieve 93 relevant publications in the time frame 1990–2024. The results showed that the number of publications on reception/perception in interlingual dubbing and subtitling has increased – especially since 2017–18 – but that it remains a fraction of the overall research published in AVT. Moreover, relatively small case studies and non-randomized sampling remain the prevalent methodologies implemented by scholars. The final section of the paper explores potential reasons for and consequences of these methodological choices. Lay summary This paper provides a review of English-language journal articles and book chapters that explore how audiences perceive and react to interlingual dubbing and subtitling. The aim is to track the evolution of research in this field over the past two decades. A total of 93 relevant publications from 1990 to 2024 were identified by applying specific inclusion and exclusion criteria and conducting searches across four databases: Scopus, BITRA, TSB, and Web of Science. The study examines two key points: 1. While there has been an increase in research on audience perception and reception of dubbing and subtitling in recent years, it still represents a relatively small portion of audiovisual translation (AVT) research. 2. Most of the studies in this area are small-scale and tend to be isolated projects. The results support both points. While there has been a notable rise in research on this topic, particularly from 2017-18 onward, it remains a minor aspect of the broader AVT field. Furthermore, small-scale case studies, often using non-random sampling methods, are predominant. The paper concludes by discussing the reasons behind the prevalence of these methods and their potential implications.